Answer:
C) 4,0
Explanation:
Basically to find zeros you set up the expression equal to zero.
First pair is (0,0) they derived this by setting the leftmost x to 0 so x=0, this meant that when x was plugged back into the equation y = x(x-4) the y value we got out was 0 because y = 0 (0-4) = 0, thus the pair (0,0).
For second pair, we set up x-4= 0, solve this to get x = 4 (add 4 to both sides). Now plug this back into full equation y= 4 (4-4)= 0, you get y=0 and your ordered pair is (4,0) which is the second pair of zero.
Zero are x-intercept where y is zero which is the main reason why we setup x=0 or x-4=0 to start with.